Magnetic nanoparticles: Co@SiO2, Co@Au and Co@Pt - Sargentelli, Vagner [UNESP]; Ferreira, Antônio A.P. [UNESP] (My University, 2011)
Nanotechnology is the understanding and control f matter at dimensions of roughly 1 - 100 nm. At the nanoscale, the properties like electrical conductivity and mechanical strength are not the same as the materials with particles in dimensions much more than 100 nm. The electronic structure changes dramatically too. Between nanomaterials, there is recently a great number of works that investing as the synthesis as the properties of the magnetic nanoparticles. The interest in these materials is due to its magnetic applications. Some of more representative magnetic materials are the metallic oxides, as some ferrites. However, the ferrites are often obtained as mixture of some oxides, which implies that the magnetic properties are not always well defined and reproducible. Thus, the researches has been turned to use of the magnetic metals, between which the cobalt. The cobalt is investigated because its high magnetic susceptility. However, this transition metal is easily oxidate in air and is toxic to human organism. For this reason, it has looked for to effect synthesis involving core - shell structures, which no to allow the oxidation of the cobalt and prevent against its toxicity. Between the shells that come being obtained it is of silica and of gold. In addition, in if treating to catalysis in a general way, the price of the cobalt and its magnetic properties are adjusted for the attainment core - shell catalysts, Cocore@Ptshell, (Co@Pt). So, the aim of this article is to present and to do an analysis of the more representative synthetic route used until the present moment to obtain the core - shell structures: Co@SiO2, Co@Au and Co@Pt.
Keywords: Co@Au; Co@Pt; Co@SiO2; Magnetic nanoparticles